2006
DOI: 10.1111/j.1365-2958.2006.05271.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo, fliC expression by Salmonella enterica serovar Typhimurium is heterogeneous, regulated by ClpX, and anatomically restricted

Abstract: Summary FliC is a natural antigen recognized by the innate and adaptive immune systems during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
190
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(199 citation statements)
references
References 73 publications
7
190
1
Order By: Relevance
“…There are several reports that the expression of FliC is downregulated in Salmonella-infected macrophages or during Salmonella infection in mice (Alaniz et al, 2006;Cummings et al, 2006;Eriksson et al, 2003). However, our data showed that FliC was detected in about 70 % of macrophages infected with the wild-type strain but almost not at all in macrophages infected with the spiC mutant.…”
Section: Discussioncontrasting
confidence: 55%
“…There are several reports that the expression of FliC is downregulated in Salmonella-infected macrophages or during Salmonella infection in mice (Alaniz et al, 2006;Cummings et al, 2006;Eriksson et al, 2003). However, our data showed that FliC was detected in about 70 % of macrophages infected with the wild-type strain but almost not at all in macrophages infected with the spiC mutant.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, integration host factor was found to repress the expression of flagellin in EPEC and EHEC when grown in DMEM (45). Similarly, studies of other bacterial pathogens suggest that while flagellin expression may occur at early stages of infection, or at specific tissue sites, flagellin expression may be reduced or even absent at later stages of infection, as was recently described for Salmonella enterica serovar Typhimurium (11).…”
Section: Discussionmentioning
confidence: 86%
“…When the pathogen Salmonella enterica serovar Typhimurium is grown under homogenous conditions in rich media, transcription of the flagellin monomer fliC is bistable, with well-defined subpopulations of fliC-OFF and fliC-ON cells (3). In this organism, a three-class transcriptional cascade orders the production of flagellar proteins (4).…”
mentioning
confidence: 99%